2016
DOI: 10.1016/j.jcin.2016.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Following Transcatheter Aortic Valve Replacement in Asian Population

Abstract: Despite anatomical features of concern, the clinical outcomes of TAVR in our Asian population were favorable in comparison with those of previously published trials and observational studies. (The Asian Transcatheter Aortic Valve Replacement Registry [Asian TAVR]; NCT02308150).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 31 publications
5
55
0
Order By: Relevance
“…We reported the mid-term results of our own modest series last year consisting of 59 patients who underwent TAVI procedure between 2010 and 2015 (22) Asian countries. The 30-day mortality in this cohort was 2.5% and the 1-year mortality was 10.8% (14).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We reported the mid-term results of our own modest series last year consisting of 59 patients who underwent TAVI procedure between 2010 and 2015 (22) Asian countries. The 30-day mortality in this cohort was 2.5% and the 1-year mortality was 10.8% (14).…”
Section: Discussionmentioning
confidence: 62%
“…The Asian Pacific TAVR Multicentre Registry (NCT02195102) enrolls patients spanning eight Asian countries from at least 10 institutions and currently has more than 1,000 patients in this database. The Asian TAVR is a Korean initiative with more than 840 patients recruited from 11 institutions spanning five Asian countries (14).…”
Section: Registry and Trialsmentioning
confidence: 99%
“…Based on data from previous registries, the proportion of patients with bicuspid AS may reach 2% to 6% (14,15). As the indication of TAVR has been expanding to younger and lower surgical-risk patients with increasing frequency of bicuspid AS, there has been increasing concern regarding the clinical outcomes of TAVR in bicuspid AS population (7)(8)(9)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a multicenter, large-scale TAVR study revealed that Asian populations had lower STS scores (5.2%), body mass index, 30-day and 1-year mortality (2.5 and 10.8%), but similar post-TAVR complications when compared to Western populations [19]. Our sample is a typical Asian population, albeit with a slightly higher STS score.…”
Section: Discussionmentioning
confidence: 70%